Metabolic targeting of EGFRvIII/PDK1 axis in temozolomide resistant glioblastoma - Velpula, Kiran K. (Oncotarget, 2017)
Glioblastomas are characterized by amplification of EGFR. Approximately half of tumors with EGFR over-expression also express a constitutively active ligand independent EGFR variant III (EGFRvIII). While current treatments emphasize surgery followed by radiation and chemotherapy with Temozolomide (TMZ), acquired chemoresistance is a universal feature of recurrent GBMs. To mimic the GBM resistant state, we generated an in vitro TMZ resistant model and demonstrated that dichloroacetate (DCA), a metabolic inhibitor of pyruvate dehydrogenase kinase 1 (PDK1), reverses the Warburg effect. Microarray analysis conducted on the TMZ resistant cells with their subsequent treatment with DCA revealed PDK1 as its sole target. DCA treatment also induced mitochondrial membrane potential change and apoptosis as evidenced by JC-1 staining and electron microscopic studies. Computational homology modeling and docking studies confirmed DCA binding to EGFR, EGFRvIII and PDK1 with high affinity. In addition, expression of EGFRvIII was comparable to PDK1 when compared to EGFR in GBM surgical specimens supporting our in silico prediction data. Collectively our current study provides the first in vitro proof of concept that DCA reverses the Warburg effect in the setting of EGFRvIII positivity and TMZ resistance leading to GBM cytotoxicity, implicating cellular tyrosine kinase signaling in cancer cell metabolism.